On emerging stock market contagion: the Baltic region - Alexakis, P; Kenourgios, D.; D. Dimitriou (Research in International Business and Finance, 2016)
This study provides new evidence on emerging stock market contagion during the Global Financial crisis (GFC) and the Euro zone Sovereign Debt Crisis (ESDC). Focusing on the three emerging Baltic markets and developed European markets, proxied by the EUROSTOXX50 stock index, we explore asymmetric dynamic conditional correlation dynamics across stable and crisis periods. Empirical evidence indicates a diverse contagion pattern for the Baltic region across the two crises. Latvia and Lithuania were contagious during the GFC, while they were insulated from the adverse effects of the ESDC. On the other hand, Estonia decoupled from the negative consequences during the global turmoil period, but recoupled during the ESDC. The results could be attributed to financial and macroeconomic characteristics of the Baltic countries before and after the turmoil periods and the introduction time of the Euro as a national currency.